Prevalence and association of sleep duration and different volumes of physical activity with type 2 diabetes: the first evidence from CHARLS - Zigui Zhou; Xuewen Tian (BMC Public Health)
Abstract Objectives This study aimed to examine the prevalence of type 2 diabetes (T2D) and the independent and joint associations of sleep duration and different volumes of physical activity (PA) with T2D in the China Health and Retirement Longitudinal Study (CHARLS). Methods The prevalence of T2D among the Chinese population aged 45 years and older was estimated for the years 2011, 2013, 2015, 2018, and 2020. Data from 2020 were used to examine the independent and joint associations of sleep duration and different volumes of PA with T2D. Sleep duration was classified into three categories: short (< 6 h/day), normal (6–8 h/day), and long (> 8 h/day). PA volumes were classified based on the IPAQ recommendations as follows: light-volume PA (LPA, < 600 MET-minutes/week), moderate-volume PA (MPA, 600–3000 MET-minutes/week), and vigorous-volume PA (VPA, > 3000 MET-minutes/week). The data were statistically analyzed using a t-test and analysis of variance (ANOVA). Multivariate logistic regression models were used to examine the independent and joint associations of PA and sleep duration with T2D. Results The prevalence of T2D in the LPA and short sleep groups increased from 13.35% (95% CI = 10.41–16.75) and 11.52% (95% CI = 10.01–13.15) in 2011 to 17.27% (95% CI = 15.09–19.62) and 16.28% (95% CI = 15.34–17.25) in 2020, respectively. Compared with LPA, VPA was associated with lower odds of T2D (Model 3, OR = 0.82, 95% CI = 0.69–0.97). Compared to individuals with normal sleep duration, those with short sleep duration had a higher likelihood of T2D (Model 3, OR = 1.10, 95% CI = 1.08–1.22), whereas long sleep duration did not show a significant association (Model 3, OR = 1.03, 95% CI = 0.86–1.23). The risk of developing T2D was approximately 35% lower for individuals with LPA and normal sleep duration compared to those with LPA and short sleep duration (Model 3, OR = 0.65, 95% CI = 0.46–0.91). In the VPA group, the mitigation effect of exercise on T2D was observed regardless of sleep duration (Model 3, short: OR = 0.73, 95% CI = 0.56–0.95; normal: OR = 0.65, 95% CI = 0.51–0.85; long: OR = 0.63, 95% CI = 0.45–0.89). Conclusions The prevalence of T2D among middle-aged and older adults in China increased substantially from 2011 to 2020. Short sleep duration is associated with higher odds of developing T2D. However, engaging in VPA mitigates this risk, even in those with insufficient sleep.